(untitled) (Zaporizhzhia Historical Review, 2021)
The article is dedicated to researching the issues of national elite structure in the end of XIX – early XX century. The author tries to analyze professional staff of the national elite, to find out why significant part of it was represented by humanitarian intellectuals, what role this intellectual category has played in national revival.